KEBUTUHAN PENGAJAR OUTDOOR ADVENTURE EDUCATION DITINJAU DARI LENSA PEDAGOGICAL CONTENT KNOWLEDGE (PCK); NARRATIVE LITERATURE REVIEW - Asep Ridwan Kurniawan; Rafdal Saeful Bakhri; Ade Evriansyah Lubis; Agus Taufiq; Yusi Riksa Yustina (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
A wealth of empirical evidence documents the positive effects associated with participating in outdoor adventure learning for students, instructors, and the wider community. Nonetheless, there has been a substantial reduction in outdoor learning opportunities for school students, possibly due to a focus on evidence-based outcomes, high standard teacher testing programs, and teachers' lack of knowledge, confidence, and expertise in outdoor teaching and learning. So that the relationship between the environment, students, and teachers needs in-depth study. Therefore, this paper presents an evidence-based model to support teaching practice, in which the focus of the study addresses the needs of outdoor adventure education (OAE) teachers in the concept of Pedagogical Content Knowledge (PCK). The result of this paper is a 'modified' PCK framework for outdoor adventure education tailored to the needs of educators.